Religion in China: Ties That Bind - Chau, Adam Yuet (China Today Ser., 2019)
Intro -- Table of Contents -- Series page -- Title page -- Copyright page -- Dedication -- Figures -- Map -- Chronology -- Acknowledgments -- Notes on Orthography and Pronunciation -- Introduction: Relationality at the Heart of Religion in China -- Why Are You Reading This Book? -- A Relational Approach to Understanding Chinese Religious Life -- What Is Religion? Do Spirits Exist? -- Spatial Expanse and Time Frame -- Statistics: The Numbers Game [Warning: User Beware!] -- The Author and the Sources -- Diverse Approaches to Studying Religion in China -- Notes -- 1: Understanding Religious Diversity: Five Modalities of Doing Religion -- Religious Diversity as Fact and Religious Pluralism as Ideology -- Modalities of Doing Religion -- Implications for Our Understanding of Religious Diversity -- Notes -- 2: Interacting with Gods, Ghosts, and Ancestors -- Efficacy and Deity-Worshiper Relationships -- Worshiping Deities -- Divination -- Appeasing "Hungry Ghosts" -- Relationships with Ancestors -- The Household as Basic Unit of Religious Engagement -- The Hosting Idiom in Chinese Religious Practices -- Notes -- 3: Festivals and Pilgrimages -- Temple Associations and Temple Festivals -- Temple Festivals and Social Relationships -- Temple Festivals and Social Heat -- Temple Festivals and Inter-Communal Rivalry -- Gods Visiting Gods: Mazu Pilgrimages in Taiwan -- Ciji Pilgrimages: Re-Territorializing Universalism -- Drawing Power from Multiple Sites: New Age Spirit Cultivation in Contemporary Taiwan -- From China to Mecca: The Hajj Pilgrimage and the Chinese State -- Longwanggou Hosts a Tree Planting Event: The Visit of Beijing Arbortourists -- Mutual Capturing -- Notes -- 4: Ritual Service Providers and Their Clients -- Ritual Service and Efficacy -- A Yinyang Master at a Funeral -- Funeral Rituals Conducted by a Daoist Troupe in Shanxi Province.